2021
DOI: 10.1038/s41598-021-91179-2
|View full text |Cite
|
Sign up to set email alerts
|

Fronto-striatal structures related with model-based control as an endophenotype for obsessive–compulsive disorder

Abstract: Recent theories suggest a shift from model-based goal-directed to model-free habitual decision-making in obsessive–compulsive disorder (OCD). However, it is yet unclear, whether this shift in the decision process is heritable. We investigated 32 patients with OCD, 27 unaffected siblings (SIBs) and 31 healthy controls (HCs) using the two-step task. We computed behavioral and reaction time analyses and fitted a computational model to assess the balance between model-based and model-free control. 80 subjects also… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
(75 reference statements)
1
3
0
Order By: Relevance
“…This may support previous findings of a disrupted arbitration mechanism in OCD patients (28,51) and might potentially be responsible for the dominance of habitual behaviours in OCD. In line with our findings, past studies have also found structural and functional alterations within the fronto-striatal circuits, particularly the mPFC, putamen and caudate responsible for the imbalance between model-free and model-based decision-making in OCD (28,52). Additionally, the mPFC is a crucial part of the dorsal cognitive CSTC circuit which contributes to habit formation and compulsivity in OCD (53).…”
Section: Discussionsupporting
confidence: 91%
“…This may support previous findings of a disrupted arbitration mechanism in OCD patients (28,51) and might potentially be responsible for the dominance of habitual behaviours in OCD. In line with our findings, past studies have also found structural and functional alterations within the fronto-striatal circuits, particularly the mPFC, putamen and caudate responsible for the imbalance between model-free and model-based decision-making in OCD (28,52). Additionally, the mPFC is a crucial part of the dorsal cognitive CSTC circuit which contributes to habit formation and compulsivity in OCD (53).…”
Section: Discussionsupporting
confidence: 91%
“…Although they achieved the same nestlet score as the other genotypes by 24 hours, they also used less of the nestlet overall compared to Ptprd WT and HT mice (Fig 4B). Future studies will evaluate Ptprd KO mice in a probabilistic learning task (PLT) which can be used to measure goal-directed versus habitual decision-making strategies in both rodent and humans [79,80], with OCD patients showing a shift towards habitual choices in this paradigm [81,82].…”
Section: Plos Onementioning
confidence: 99%
“…The DLPFC is involved in executive functions and emotion regulation ( 69 ). It is a key node in the FPN involved in cognitive control and the fronto-striatal loop in habitual behavior ( 70 , 71 ). The decreased FC in the bilateral DLPFC may indicate a top-down disruption between these networks and underlie the pathophysiology and clinical symptoms of OCD ( 72 ).…”
Section: Discussionmentioning
confidence: 99%